Strong Convergence Iterative Algorithms for Equilibrium Problems and Fixed Point Problems in Banach Spaces - Shenghua Wang; Shin Min Kang (Abstract and Applied Analysis)
We first introduce the concept of Bregman asymptotically quasinonexpansive mappings and prove that the fixed point set of this kind of mappings is closed and convex. Then we construct an iterative scheme to find a common element of the set of solutions of an equilibrium problem and the set of common fixed points of a countable family of Bregman asymptotically quasinonexpansive mappings in reflexive Banach spaces and prove strong convergence theorems. Our results extend the recent ones of some others.